Brace Effectiveness Is Related to 3-Dimensional Plane Parameters in Patients with Adolescent Idiopathic Scoliosis. (6th January 2021) - Kwan, Kenny Yat Hong; Cheung, Amy Ka Po; Koh, Hui Yu; Cheung, Kenneth Man Chee
Abstract : Background: Although scoliosis is a 3-dimensional (3D) deformity, little research has been performed on the use of 3D imaging in brace curve correction. The purpose of the present study was to determine the effect of axial-plane parameters on the outcomes of bracing with a thoracolumbosacral orthosis for adolescent idiopathic scoliosis. Methods: This prospective longitudinal cohort study included patients with adolescent idiopathic scoliosis who fulfilled the criteria for bracing according to the Scoliosis Research Society, and was conducted from the time the patient began wearing the brace through a minimum follow-up of 2 years or until a surgical procedure was performed. Radiographs made with use of an EOS Imaging System were used to reconstruct 3D images of the spine at the pre-brace, immediate in-brace, 1-year in-brace, and latest follow-up out-of-brace stages. Univariate and multiple linear regressions were performed to determine the association between axial rotation correction and curve progression at the time of the latest follow-up. Logistic regressions were performed to model the probability of risk of progression. Results: Fifty-three patients were enrolled, and 46 patients were included in the analysis. At the time of the latest follow-up, 30 patients did not experience curve progression and 16 patients had curve progression. There was no difference in baseline demographic characteristics between groups. For the transverse-plane parameters, there was a significant difference between non-progression and progression groups in pre-brace apical vertebral rotation (4.5° ± 11.2° compared with −2.4° ± 9.8°, respectively; p = 0.044) and in 1-year in-brace apical vertebral rotation correction velocity (2.0° ± 5.0°/year compared with −1.7° ± 4.4°/year, respectively; p = 0.016). Logistic regression analysis showed that pre-brace apical vertebral rotation (odds ratio, 1.063; 95% confidence interval, 1.000 to 1.131; p = 0.049) and 1-year in-brace apical vertebral rotation correction velocity (odds ratio, 1.19; 95% confidence interval, 1.021 to 1.38; p = 0.026) were associated with an increased risk of curve progression. There was no difference in Scoliosis Research Society 22-Item scores between patients who experienced curve progression and those who did not. Conclusions: In this prospective study, we demonstrated that axial-plane parameters and the correction of these parameters during bracing are related to the successful use of the brace. Level of Evidence: Prognostic Level II . See Instructions for Authors for a complete description of levels of evidence.